Achieving sustainable indium recycling: Highly selective separation from acidic tin-rich solutions by solvent extraction - Zhen Yang; Huan Luo; Tongda Deng; Peng Liang; Tengteng Shi; Fengkang Wang; Xianjun Lei; Wenlong Jiang; Bin Yang; Baoqiang Xu (Journal of Environmental Chemical Engineering, 2026)

Fluorescence signatures track bidirectional DOM-POM interconversion across a mangrove estuarine salinity gradient - Lu Yan; Zhihan Yang; Xianjun Xie; Kang Peng; Yamin Deng; Yiqun Gan; Qinghua Li; Yanpeng Zhang (Marine Chemistry, 2026)

Mechanisms of iodate reduction by sediment siderite and its contribution to iodide enrichment in groundwater - Shilin Zhao; Junxia Li; Yinchun Su; Daolian Deng; Wenyi Zhang; Qian Liao; Xianjun Xie; Yanxin Wang (Chemical Geology, 2026)

Ellagic acid improves growth performance and alleviates liver-gut injury of juvenile hybrid snakehead (Channa argus × Channa maculata) via antioxidative, anti-inflammatory, and gut microbiota modulating effect - Xianjun Zhou; Fujia Zhang; Xiaoyu Deng; Zhijun Luo; Julin Wang; Jian Zhao; Shuzhan Fei (Aquaculture, 2026)

Source-specific organic matter modulates Anammox via humic-like DOM in mangrove sediments: Implications for eutrophication mitigation - Chi Zhang; Yamin Deng; Weichen Xia; Lu Yan; Xianzhong Ke; Yanpeng Zhang; Qinghua Li; Xianjun Xie; Yanxin Wang (Environmental Pollution, 2026)

A coupled fluorescence assay for high-throughput screening of polyurethane-degrading enzymes - Liujun YANG; Xianjun DENG; Renju LIU; Jianyang LI; Junyao ZHAI; Xiaoxiao MA; Shiyang YOU; Qinghao HE; Arthur K.L. LIN; Zongze SHAO; Hongyuan LU (Journal of Hazardous Materials, 2026)

Decoding microbial-mediated sulfur transformation pathways in mangrove wetland: Metagenomic and hydrogeochemical insights - Lu Yan; Yushu Su; Xianjun Xie; Kang Peng; Pan Zhang; Yamin Deng; Yiqun Gan; Qinghua Li; Yanpeng Zhang (Environmental Research, 2026)

Spatial-Temporal Dynamics of Dongzhaigang Mangrove Forests on Hainan Island, China: Evidence from Landsat Observations (1988–2019) - Bing Tu; Kang Peng; Xianjun Xie; Lu Yan; Yamin Deng; Yiqun Gan; Qinghua Li (Journal of Earth Science, 2026)

Probiotic combination alleviates ulcerative colitis by targeting abnormal enrichment of Enterobacteriaceae and improvement of amino acid metabolic disorders - Jiaxin You; Zhentao Yao; Tingting Chen; Yuhong Yang; Nuobei Zhang; Jingwen Deng; Shiwen Huang; Xianjun Dai; Zheng Ruan (Food Bioscience, 2026)

Coastal SOM degradation regulates the transformation of iron in mangrove sediments and its environmental significance - Lu Yan; Jingxian Zhang; Xianjun Xie; Kang Peng; Yamin Deng; Yiqun Gan; Qinghua Li; Yanpeng Zhang (Applied Geochemistry, 2025)

Unveiling the antibacterial potential of anthocyanins – a comprehensive review on this natural plant extract - Haotian Deng; Xianjun Meng; Bo Xue; Lianwei Li (Critical Reviews in Food Science and Nutrition, 2025)

Sedimentary Evolution and Mangrove Dynamics in Dongzhai Harbor, Hainan Island since the Late Pleistocene - Xueyan Yan; Yamin Deng; Xianzhong Ke; Kang Peng; Xianjun Xie; Yiqun Gan; Qinghua Li (Journal of Earth Science, 2025)

Advances in groundwater quality and health studies: A comprehensive review - Yanxin Wang; Yamin Deng; Jingwei Zhang; Bing Yan; Ziyi Xiao; Ruiyu Fan; Xianjun Xie (Science China Earth Sciences, 2025)

Improved physics-informed neural network for reactive transport modeling of groundwater arsenic enrichment - Fang Deng; Jichun Wu; Yun Yang; Junxia Li; Xianjun Xie; Jianguo Jiang; Xiaobin Zhu (Science China Earth Sciences, 2025)

Marine octopus: global distribution, extraction methods, bioactive biomaterials, and biomedical applications - Mengfei Li; Zhihong Deng; Kun Cheng; Xianjun Fu; Xiuxue Li (Frontiers in Marine Science, 2025)
Octopus, an abundant marine species with diverse applications, is attracting growing attention for its unique biological characteristics and potential utilization in food science and biotechnology. Octopus contain amino acids, active peptides, fatty acids and trace elements and these bioactives exhibit a wide range of effects, including anti-bacterial, anti-tumor, antioxidant and anti-aging activities. The structure of octopus arm and suckers provides biomimetic design inspiration for tissue engineering and the regenerative ability of octopus provides reference for research in biomedical material. Therefore, this review systematically summarizes the research progress on octopus resource distribution, extraction methods, nutrients, bioactive compounds substances and research on regeneration material, aiming to promote the development and utilization of octopus resources. Firstly, the extractions methods of octopus were systematically reviewed. Secondly, seven kinds of nutrients concluded were introduced to reveal the nutritional components of octopus. Finally, the application of octopus in biotechnology and the research progress on their regenerative ability were summarized. This review provides a basis and reference for octopus functional nutrients and application of octopus biomedical materials.

Quantifying the fate of biogenic elements in mangrove aquifers: Insights from reactive transport modeling under saltwater-freshwater mixing - Kang Peng; Lu Yan; Xianjun Xie; Yamin Deng; Yiqun Gan; Qinghua Li; Yanpeng Zhang; Xianqiang Tang (Water Research, 2025)

Spatial distribution and formation mechanisms of high‑iodine groundwater throughout China - Junxia Li; Shilin Zhao; Zhou Jiang; Xianjun Xie; Yamin Deng; Liang Shi; Andreas Kappler; Philippe Van Cappellen; Yanxin Wang (Earth-Science Reviews, 2025)

Processing pathways of organic matter under methanogenic conditions and its influence on arsenic mobilization in aquifers - Xiaofang Yuan; Yamin Deng; Yao Du; Jiangkai Xue; Kunfu Pi; Yijun Yang; Yuxiao Xu; Xianjun Xie; Yanxin Wang (Journal of Hydrology, 2025)

Molecular characteristics of dissolved organic phosphorus in watershed runoff: Coupled influences of land use and precipitation - Zhanyao Shi; Yao Du; Hongni Liu; Yamin Deng; Yiqun Gan; Xianjun Xie (Journal of Environmental Sciences, 2025)

Hydrogeochemical dynamics under saltwater-freshwater mixing in a mangrove wetland over tidal cycles - Kang Peng; Lu Yan; Xianjun Xie; Yamin Deng; Yiqun Gan; Yanpeng Zhang (Science of The Total Environment, 2024)

Anthocyanin-rich lingonberry extract ameliorates high fat diet-induced intestinal damage by regulating the gut microbiota-intestinal stem cell axis via Wnt/PPAR signaling - Jiayi She; Xiaobin Hu; Jiannan Deng; Shuhang Fan; Qianyi Zhang; FuLi Nie; Jialei Zhang; Mark Christian; Zhenyu Wang; Xianjun Dai (Food Bioscience, 2024)

Evolution of the Mangrove Wetland since the Holocene: Current Progress and Future Perspectives - Xueyan Yan; Xianzhong Ke; Qinghua Li; Yiqun Gan; Xianjun Xie; Yamin Deng (Journal of Earth Science, 2024)

Insights into nitrogen biogeochemical cycling in mangrove wetland from Genome-Resolved metagenomic sequencing - Lu Yan; Yunlei Kuang; Xianjun Xie; Kang Peng; Yamin Deng; Yiqun Gan; Qinghua Li; Yanpeng Zhang (Journal of Hydrology, 2024)

Unraveling roles of dissolved organic matter in the co-occurrence of arsenic and ammonium in Quaternary alluvial-lacustrine aquifers - Xueyan Yan; Yamin Deng; Yao Du; Xiaofang Yuan; Yuxiao Xu; Xianjun Xie; Yanxin Wang (Applied Geochemistry, 2024)

Tanshinone IIA, originated from Salvia miltiorrhiza, activated EPO/EPOR-JAK2-STAT5 pathway in rat blood deficiency therapy - Miao Wang; Zhihong Deng; Congwei Shi; Kun Cheng; Runxiang Zhai; Xiuxue Li; Xianjun Fu (South African Journal of Botany, 2024)

Multiple isotope approach elucidates the calcium enrichment of groundwater in the central Yangtze River Basin - Yijun Yang; Yamin Deng; Xianjun Xie; Yanxin Wang (Applied Geochemistry, 2024)

Unravelling the impacts of soluble Mn(III)-NOM on arsenic immobilization by ferrihydrite or goethite under aquifer conditions - Yuxi Zhang; Yamin Deng; Jiangkai Xue; Yihan Cheng; Yulun Nie; Kunfu Pi; Yao Du; Xianjun Xie; Jianbo Shi; Yanxin Wang (Journal of Hazardous Materials, 2024)

Predicting geogenic groundwater arsenic contamination risk in floodplains using interpretable machine-learning model - Ruiyu Fan; Yamin Deng; Yao Du; Xianjun Xie (Environmental Pollution, 2024)

Contrasting occurrence of arsenic concentrations in Quaternary aquifers inside and outside the oxbow lakes along the middle reaches of the Yangtze river - Ruiyu Fan; Yamin Deng; Jiangkai Xue; Yuxiao Xu; Xiaofang Yuan; Xueyan Yan; Chi Zhang; Yao Du; Xianjun Xie (Applied Geochemistry, 2024)

Manganese mobilization from sediment to groundwater in alluvial-lacustrine aquifer system along the lower reaches of Han River - Yijun Yang; Yamin Deng; Yu Xu; Jiaqi Yan; Yao Du; Xianjun Xie; Yanxin Wang (Journal of Hydrology, 2023)

Effects of reservoir construction on optical and molecular characteristics of dissolved organic matter in a typical P-contaminated river - Hongni Liu; Yao Du; Zhanyao Shi; Yamin Deng; Yiqun Gan; Xianjun Xie (Chemosphere, 2023)

Organic matter degradation and arsenic enrichment in different floodplain aquifer systems along the middle reaches of Yangtze River: A thermodynamic analysis - Yijun Yang; Qian Wang; Jiangkai Xue; Shuhang Tian; Yao Du; Xianjun Xie; Yiqun Gan; Yamin Deng; Yanxin Wang (Water Research, 2023)

Coupled effects of sedimentary iron oxides and organic matter on geogenic phosphorus mobilization in alluvial-lacustrine aquifers - Xinxin Zhang; Xianzhong Ke; Yao Du; Yanqiu Tao; Jiangkai Xue; Qinghua Li; Xianjun Xie; Yamin Deng (Science of The Total Environment, 2023)

N-Fluorobenzenesulfonimide as a multifunctional electrolyte additive for co-stabilizing dual-electrodes of lithium metal batteries with enhanced electrochemical performance - Xianjun Weng; Yanyang Qin; Xinyu Da; Yuanjun Zhao; Xuetian Deng; Bo Wen; Manying Cui; Xiangkai Yin; Yaqiong Su; Jiangxuan Song; Shujiang Ding; Xiaofei Hu; et al. (Chemical Engineering Journal, 2023)

Groundwater discharge and saltwater-freshwater mixing in a mangrove wetland over tidal cycles: A field and modeling study - Kang Peng; James W. Heiss; Xianjun Xie; Lu Yan; Yamin Deng; Yiqun Gan; Qinghua Li; Yanpeng Zhang (Journal of Hydrology, 2023)

Isotopic and spectral signatures unravel the sources, preservation and degradation of sedimentary organic matter in the Dongzhai Harbor mangrove estuary, southern China - Lu Yan; Xianjun Xie; James W. Heiss; Kang Peng; Yamin Deng; Yiqun Gan; Qinghua Li; Yanpeng Zhang (Journal of Hydrology, 2023)

Effects of mannoprotein on the stability and in vitro digestion of cyanidin-3-glucoside - Meizhi Wan; Sixu Lin; Chang Tan; Mingyue Wang; Yuqi Tong; Yang Zhao; Yanwen Kong; Haotian Deng; Xianjun Meng; Yan Ma (Food Chemistry, 2023)

Novel insight into iodine enrichment in alluvial-lacustrine aquifers: Evidence from stable carbon and iron isotopes - Yuxiao Xu; Yamin Deng; Yao Du; Jiangkai Xue; Xiaofang Yuan; Yipeng Luo; Xianjun Xie; Yanxin Wang (Journal of Hydrology, 2023)

Genesis of geogenic contaminated groundwater: As, F and I - Yanxin Wang; Junxia Li; Teng Ma; Xianjun Xie; Yamin Deng; Yiqun Gan (Critical Reviews in Environmental Science and Technology, 2021)